Producción de contenidos transmedia, una estrategia innovadora - Saavedra-Bautista, Claudia; Cuervo-Gómez, William Oswaldo; Mejía-Ortega, Iván Darío (Revista Científica, 2017)
The paper presents a literature review on the state of the art of transmedia and its application in different scenarios. This review is carried out as a starting point for the development of the project "collective intelligence practices for building transmedia narratives", which aims to determine strategies for generating collective intelligence of transmedia narratives. It explores tactics transmedia production and collaborative processes that arise within its development. Also, successful experiences that are committed to the incursion of this new practice in education are discussed. It is concluded that as the transmedia production trends have become a social phenomenon that comes amid digital convergence, offering opportunities to see and rethink reality through creative and collaborative writing; involving various formats and new content production, diversifying stories and enable participation and interaction of multiple analog and digital media.